RITUAL OF HUMAN SACRIFICE IN AZERBAIJAN BURIALS DURING THE LATE BRONZE – EARLY IRON AGES - Arzu Abdullayeva, (International Journal of Innovative Technologies in Social Science, 2024)
Burial customs such as inhumation and cremation were studied in a large number of kurgans, stone-box and earthen graves belonging to Khojaly-Gadabay, Nakhchivan and Talish - Mughan archaeological cultures in Azerbaijan, as well as cenotaph and skeletonless graves were studied. The dead were buried in different directions, situations, alone, in pairs, or collectively. The custom of human sacrifice in the territory of Azerbaijan was observed in the Boyuk Borsunlu, Akhmakhi, Baimsarov, Dovshanli, Garabulag, Sarichoban kurgans, Ganja and Goygol kurgans, as well as Veri, Joni, Chilakhana, Shir-shir and other stone box graves. Besides the main corpse, the sacrifices who will accompany him to the hereafter, are also buried. One of the facts proving the sacrifice of foreign slaves is the anthropological features of the sacrifices in the Akhmakhi kurgans number 1 and 2. Another interesting fact is that in such graves, the main corpse was usually buried in an extended position, while the accompanying corpses were buried in a seated position. These monuments, which date back to the end of the 2nd millennium and the beginning of the 1st millennium B.C., give an idea of not only the religious outlook, socio-economic situation, but also the military situation of the people of that time.